Ukama Ustawi/AICCRA I2G 2024 Innovation Challenge - BongoHive (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Ukama Ustawi/I2G Open Innovation Challenge (OIC) was a collaborative initiative led by the International Water Management Institute (IWMI), the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), and the Consultative Group on International Agricultural Research (CGIAR). Its primary goal was to equip Early Career Researchers (ECRs) and practitioners in East and Southern Africa with the tools to address critical issues in agricultural water management, soil health, sustainability, and environmental science. Through this initiative, ECRs were encouraged to develop demand-driven research solutions that tackled real-life challenges in Climate-smart Agriculture and Climate Information Systems (CSA-CIS).